2020
DOI: 10.1002/ppap.201900246
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of nanocrystalline graphene/graphite: An overview of synthesis and applications

Abstract: Nanocrystalline graphite/graphene (NCG) has been studied well before graphene was successfully produced in 2004. Despite the fact that NCG thin films cannot reach the high performance of large‐area graphene in some of its properties, they are able to provide significant benefits for various applications, besides being easier to produce and integrate into devices with current processing technologies. We present here, a comprehensive account of the large variety of synthesis methods, as well as of the already la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…A proposed nomenclature for the diversified carbonic structures can be consulted in [23]. While respecting the aforementioned nomenclature as much as possible and considering its various characterizations [24][25][26], we define the material used in this work as bulk-NCG: a thick and hard carbonic film consisting of 3D randomly orientated, graphite nanocrystals with a dominant turbostratic packing [27] Thin films belonging to the broad class of NCG [27] have shown promise in applications such as: field emis-sion [28], electrochemical sensing [25,29,30], photodetection [31,32], nanoelectromechanical (NEM) switching [19], fabrication of microelectromechanical (MEM) resonators [20], protective coating [33] or gas separation [34]. The inhomogeneous conductive pathways formed by the sp 2 domains provide the material with a special functionality and a high conductivity response to small strains [10,18,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proposed nomenclature for the diversified carbonic structures can be consulted in [23]. While respecting the aforementioned nomenclature as much as possible and considering its various characterizations [24][25][26], we define the material used in this work as bulk-NCG: a thick and hard carbonic film consisting of 3D randomly orientated, graphite nanocrystals with a dominant turbostratic packing [27] Thin films belonging to the broad class of NCG [27] have shown promise in applications such as: field emis-sion [28], electrochemical sensing [25,29,30], photodetection [31,32], nanoelectromechanical (NEM) switching [19], fabrication of microelectromechanical (MEM) resonators [20], protective coating [33] or gas separation [34]. The inhomogeneous conductive pathways formed by the sp 2 domains provide the material with a special functionality and a high conductivity response to small strains [10,18,35].…”
Section: Introductionmentioning
confidence: 99%
“…They obtained significant sensitivity enhancement by increasing the substrate temperature (from 525 ∘ C to 600 ∘ C) during the plasma process and, in accordance with the assumed tunneling based sensing mechanism, concluded that the key to that enhancement was the higher nucleation density, lower grain size and larger initial tunneling distance that resulted thereby. It is indeed known the beneficial effect of a higher substrate temperature on the film nucleation density [19,27,36].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene–polymer can be used to prepare thin films which find applications such as sensors, shielding, field-effect transistors, photodetectors, and gas separation membranes [ 214 ]. A thin film was prepared using GO with poly[2,5-bis(3-tetradecylthiophen-2-yl)thieno[3,2-b]thiophene] for an NO 2 sensor [ 215 ].…”
Section: Applicationsmentioning
confidence: 99%
“…The first step was the fabrication and physical/structural characterization of the NCG, as to provide useful data for the correct modelling of the material in the EM simulator used for the design of the antennas. The NCG deposition process was performed on the NANOFAB 1000 system (Oxford Instruments, UK), using the PECVD method [18]. The Si/SiO2 wafer was loaded in the preheated reactor (200°C) and heated up to 900°C at a ramp rate of 15°C/min in an Ar+H2 (5%) atmosphere.…”
Section: Ncg Thin Films Fabrication and Characterizationmentioning
confidence: 99%